"It's Almost Like Bis, Pans Kind of Stick Together:" Bi + Belonging and Community Connection. Issue 2 (18th August 2021) - Gonzalez, Kirsten A.; Flanders, Corey E.; Pulice-Farrow, Lex; Bartnik, Alma
Abstract: Belonging and community connection are important for all people, but are particularly important for bi+ (including bisexual, pansexual, queer, and other plurisexual) individuals due to experiences of anti-bisexual stigma and delegitimization by both heterosexual and lesbian, gay, bisexual, transgender, and queer (LGBTQ+) communities. A gap in the literature exists regarding bi + people's definitions and processes of locating bi + belonging and community connection. The current research addresses this gap in the literature, investigating these topics through a qualitative focus group project with 46 bi + individuals. Using a modified constructivist grounded theory approach, results from nine focus groups yielded four core categories depicting experiences of belonging and community connection for bi + participants, including: 1) Process and pathways to belonging; 2) Barriers to belonging; 3) Distinct offerings of bisexual-specific community; and 4) Unique belonging experiences of bisexual Black, Indigenous, and other People of Color (BIPOC). Findings from the current study serve as a call to action where important directions for how heterosexual and LGBTQ + communities can create more affirming and welcoming spaces for bi + community members are provided.